Procedural Modelling of Urban Road Networks - Beneš, Jan; Wilkie, Alexander; Křivánek, Jaroslav (Computer graphics forum, 2014)
We present a model for growing procedural road networks in and close to cities. The main idea of our paper is that a city cannot be meaningfully simulated without taking its neighbourhood into account. A simple traffic simulation that considers this neighbourhood is then used to grow new major roads and to influence the locations of minor road growth. Waterways are introduced and used to help position the city nuclei on the map. The resulting cities are formed by allowing several smaller settlements to grow together and to form a rich road structure, much like in real world, and require only minimal per‐city input, allowing for batch generation. We present a model for growing procedural road networks in and close to cities. The main idea of our paper is that a city cannot be meaningfully simulated without taking its neighbourhood into account. A simple traffic simulation that considers this neighbourhood is then used to grow new major roads and to influence the locations of minor road growth. Waterways are introduced and used to help position the city nuclei on the map. The resulting cities are formed by allowing several smaller settlements to grow together and to form a rich road structure, much like in real world, and require only minimal per‐city input, allowing for batch generation.